AYUSH-64 as an adjunct to standard care in mild to moderate COVID-19: An open-label randomized controlled trial in Chandigarh, India - Harbans Singh; Sumit Srivastava; Babita Yadav; Amit K. Rai; Sophia Jameela; Sanuj Muralidharan; Rijin Mohan; Shikha Chaudhary; Richa Singhal; Rakesh Rana; Shruti Khanduri; Bhagwan S. Sharma; et al. (Elsevier, 2022)
Objective: To determine the therapeutic efficacy and safety of AYUSH-64 as an add-on to standard care in mild to moderate COVID-19. Design setting, and interventions: This open-label randomized controlled parallel-group trial was conducted at a designated COVID care centre in India in 80 patients diagnosed with mild to moderate COVID-19 and randomized into two groups. Participants in the AYUSH-64 add-on group (AG) received AYUSH-64 two tablets (500 mg each) three times a day for 30 days along with standard conventional care. The control group (CG) received standard care alone. Main outcome measures: Proportion of participants who attained clinical recovery on day 7, 15, 23 and 30, proportion of participants with negative RT-PCR assay for COVID-19 at each weekly time point, change in pro-inflammatory markers, metabolic functions, HRCT chest (CO-RADS category) and incidence of Adverse Drug Reaction (ADR)/Adverse Event (AE). Results: Out of 80 participants, 74 (37 in each group) contributed to the final analysis. Significant difference was observed in clinical recovery in the AG (p < 0.001 ) compared to CG. Mean duration for clinical recovery in AG (5.8 ± 2.67 days) was significantly less compared to CG (10.0 ± 4.06 days). Significant improvement in HRCT chest was observed in AG (p = 0.031) unlike in CG (p = 0.210). No ADR/SAE was observed or reported in AG. Conclusions: AYUSH-64 as adjunct to standard care is safe and effective in hastening clinical recovery in mild to moderate COVID-19. The efficacy may be further validated by larger multi-center double-blind trials.